2002
DOI: 10.1046/j.1365-2648.2002.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing audit in palliative care: an action research approach

Abstract: Combining the cyclical nature of action research methodology and the audit process with Lewin's change theory provided a clear conceptual framework for the research. This approach would be applicable in a range of health care settings to bring about improvements in quality management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…However, a critical and unresolved barrier was the top-down approach to decision making, which hindered the use of the POS within the hospice setting. This finding supports previous work by Cooper and Hewison (2002) who identified 'good relationships with management…as crucial to success'. A good relationship with managers involves management having both an awareness of the extra time needed to implement new outcome measures and providing the appropriate resources and practical support to use the measures and carry out data analysis (Cheater and Keane, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a critical and unresolved barrier was the top-down approach to decision making, which hindered the use of the POS within the hospice setting. This finding supports previous work by Cooper and Hewison (2002) who identified 'good relationships with management…as crucial to success'. A good relationship with managers involves management having both an awareness of the extra time needed to implement new outcome measures and providing the appropriate resources and practical support to use the measures and carry out data analysis (Cheater and Keane, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Here the benefits of implementing the measure had to be easily identifiable for staff to feel its continued use was worthwhile in improving care. The timely feedback of results is, therefore, very important (Cooper and Hewison, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This methodological approach is of special relevance in palliative care and education [3134], particularly in terms of community-based interventions aimed at improving change [3437]. Following the action-research approach, the education program was tailored to the specific context of its implementation [38].…”
Section: Methodsmentioning
confidence: 99%
“…'Top down' management approaches, whereby audit is imposed upon professionals by managers, or others in positions of power, has led to difficulties in implementing audit as professionals do not feel involved in the process of change (Hunt 1993). However, 'bottom up' management can encourage more equal power sharing, ownership of the process and in doing so can improve teamwork (Cooper & Hewison 2002). For example, a comparative study of audit implementation in two contrasting care setting found 'top down' implementation coupled with hierarchical management styles inhibited the use of audit outcome measures.…”
Section: Journal Of Health and Social Policymentioning
confidence: 99%